Hydrogen Evolution: High‐Performance Hydrogen Evolution by Ru Single Atoms and Nitrided‐Ru Nanoparticles Implanted on N‐Doped Graphitic Sheet (Adv. Energy Mater. 26/2019). Issue 26 (12th July 2019) - Tiwari, Jitendra N.; Harzandi, Ahmad M.; Ha, Miran; Sultan, Siraj; Myung, Chang Woo; Park, Hyo Ju; Kim, Dong Yeon; Thangavel, Pandiarajan; Singh, Aditya Narayan; Sharma, Pankaj; Chandrasekaran, Selvaraj Selva; Salehnia, Foad; et al.
Abstract : In article number1900931, Jitendra N. Tiwari, Miran Ha, Kwang S. Kim, and co‐workers report a hydrothermal/pyrolysis process to synthesize ruthenium single atoms (SAs) and N‐doped‐graphitic(GN )‐shell‐covered nitrided‐Ru nanoparticles (NPs) planted on a melamine‐derived GN matrix {[Ru(SA)+Ru(NP)@RuN x @GN ]/GN }, exhibiting superior hydrogen evolution reaction activity and outstanding durability in both acidic and basic media.